Monitoring Server dengan Prometheus dan Grafana serta Notifikasi Telegram - Dede Rahman; Hidra Amnur; Indri Rahmayuni (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2020)
The network administrator is a person who is responsible for managing computer networks. One of the duties of a network administrator is network monitoring because errors on the server and services running on the server cannot be known when it happened. This can be difficult if the administrator is far from a surveillance center. This situation can be fatal if there is an error on the server and suddenly the service from the server is not running properly without being noticed because the network administrator is not on the spot. By utilizing Prometheus and Grafana with a telegram notification system that uses a Linux-based server, network administrators can get information on server conditions and services running on the server quickly. The result obtained is a system that is able to assist network administrators in monitoring servers and services that are running on the server anytime and anywhere to keep servers and services running on the server stable even though the network administrator is not in the monitoring center